The Influence of Serbian Ethnological Scientific Thought on the Development of Macedonian Ethnology - Malinov (FYR Macedonia), Zorančo (Bulletin of the Institute of Ethnography SASA; Vol 66 No 1 (2018): Historical Retrospectives of Ethnology and Anthropology, 2018)
The establishment of appropriate higher educational and scientific institutions (where ethnology was present as a science), was enabled by the formation of the Macedonian state as a constitutive unit of the Yugoslav Federation at the end of the World War II. The educational staff that taught the course ‘Ethnology’, as well as the curators who worked in the museums, were ethnologists who graduated from the Faculties of Philosophy in Belgrade and Skopje, which were functioning as a part of the Belgrade University in the interwar era. The influence of the Serbian ethnological science on Macedonian ethnology was also felt after the appearance of the ethnological staff who got their titles as graduated ethnologist or PhDs of ethnological science from the Skopje University. The expert literature which Macedonian ethnologist were using during the entire second half of the past century mainly came from the Serbian scientific thought and literature which was also used by Serbian ethnologists. Among the current educational and scientific staff in the Republic of Macedonia who obtained a doctoral degree from the Skopje University, a number of them presented their master thesis at the Belgrade University, and they use and recommend the works of significant Serbian ethnologists to their students. Key words: Serbian ethnology, Serbian anthropological and geographical school, Macedonian ethnology, development, influence